2018
DOI: 10.1038/s41598-018-31936-y
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral innate immune response in non-myeloid cells is augmented by chloride ions via an increase in intracellular hypochlorous acid levels

Abstract: Phagocytes destroy ingested microbes by producing hypochlorous acid (HOCl) from chloride ions (Cl−) and hydrogen peroxide within phagolysosomes, using the enzyme myeloperoxidase. HOCl, the active ingredient in bleach, has antibacterial/antiviral properties. As myeloperoxidase is needed for HOCl production, non-myeloid cells are considered incapable of producing HOCl. Here, we show that epithelial, fibroblast and hepatic cells have enhanced antiviral activity in the presence of increasing concentrations of sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 27 publications
0
73
0
3
Order By: Relevance
“…Of note, enhanced antimicrobial MΦ activity with high Na + is not restrained to anti-parasitic defenses but is also operative against E. coli [1,14]. Moreover, there is evidence that increased extracellular Na + helps in antigen degradation [15] and fighting viral infections [16,17]. In addition, elevated Na + levels prime malignant cells for apoptosis [18,19] and augment the cytotoxic potential of death receptors in cancer cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, enhanced antimicrobial MΦ activity with high Na + is not restrained to anti-parasitic defenses but is also operative against E. coli [1,14]. Moreover, there is evidence that increased extracellular Na + helps in antigen degradation [15] and fighting viral infections [16,17]. In addition, elevated Na + levels prime malignant cells for apoptosis [18,19] and augment the cytotoxic potential of death receptors in cancer cells [20].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, hypertonic saline solution inhibits SARS-CoV-2 virus replication in Vero cells due to perturbation in one or several steps of the virus intracellular cycle. NaCl is known to drive type I interferon signalling in macrophages, and that elevated concentrations of NaCl enhance the production of HOCl in non-myeloid cells 14,50 . Hypertonic saline solution decreased Respiratory syncytial virus infection and pro-inflammatory response such as IL-6 and IL-8 release in cultures of human respiratory epithelial lines 51 .…”
Section: Nacl Induces Cell Membrane Depolarization In a Dose-dependenmentioning
confidence: 99%
“…These ionic interactions could in principle be affected by increasing the ionic strength and could be used to inhibit the interaction of the virus with the host cell. Moreover, the potential antiviral activity, in vitro, of sodium chloride (NaCl) has been already studied for RNA viruses, such as mengovirus 13 , respiratory syncytial virus, influenza A virus, human coronavirus 229E and coxsackievirus B3, and also for DNA virus, like herpes simplex virus-1 and murine gammaherpesvirus 68 14 . Furthermore, a randomised controlled clinical trial studying the effectiveness of the treatment for viral upper respiratory tract infection, using hypertonic saline nasal irrigation and gargle (HSNIG) 15 , observed a decrease in the duration of illness, over-the-counter medications use, transmission within household contacts and viral shedding 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We also recently reported that epithelial cells mount an antiviral effect by producing hypochlorous acid (HOCl) from chloride ions [3]. HOCl is the active ingredient in bleach.…”
mentioning
confidence: 99%
“…All the viruses we tested were inhibited in the presence of NaCl. The human viruses we tested were: DNA/enveloped: herpes simplex virus; RNA/enveloped: human coronavirus 229E (HCoV-229E), respiratory syncytial virus, influenza A virus; and RNA/non-enveloped: coxsackievirus B3 [3].…”
mentioning
confidence: 99%